Clinical variants and mechanisms of violations of family health in women from various addictive status - Savina, M. V. (Journal of Education, Health and Sport, 2016)
Savina M. V. Clinical variants and mechanisms of violations of family health in women from various addictive status. Journal of Education, Health and Sport. 2016;6(10):772-784. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.259453 http://ojs.ukw.edu.pl/index.php/johs/article/view/4194 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. UDC 616.89-008.48:616-055.2 CLINICAL VARIANTS AND MECHANISMS OF VIOLATIONS OF FAMILY HEALTH IN WOMEN FROM VARIOUS ADDICTIVE STATUS M. V. Savina V. N. Karazin Kharkov National University, Ukraine Abstract Purpose – identification of clinical variants and mechanisms for the formation of family health disorders in women with different addictive status, to identify further targets of psychocorrection. Contingent and methods. Through clinical psychological and psychodiagnostics methods, 371 married couple who applied for help from the violation of family relationships were examined. Among them 321 families, were manifestations of addictive behavior (AB) in women (IG1), while the other 50 families – normative indicators AB in women (IG2). As a comparison group (CG) examined 50 relatively harmonious families. Results. Two options family health disorders in families, depending on the presence / absence of women socially acceptable forms of AB, were singled out. At first, stress-destructive, version, observed the couple IG2, there were pathologically congruent continuous infringement of becoming the family at all stages and phases of its development, with a rod lesions psychological and socio-psychological and lesions social components, and a burden in the form of biological component of mental health component that supported and strengthened existing distress. The interaction of these factors on a "vicious circle" induced development of each other, thus creating a chain of negative impacts. For the other, addictive-pseudocompensation, option (spouse IG1) was characterized of one-vector-inconsistent mosaic abuse formation of family processes with rod defeat of the psychological component of family health, influence of socio-psychological and social components, and violations of mental component of the biological component as AB in women, which became a pathological pseudocompensation way of leveling and emotional stress and perform buffer function on the level of its severity. Conclusion. The data were assigned us a basis for developing the psychological treatment and support family health of women in AB. Keywords: violation of family health, women, addictive behavior, a married couple.